FROM LITERARY LITERACY TO THE STUDENT-AUTHOR FORMATION - Leite Barbosa, Raquel Lazzari [UNESP]; Lopes de Souza, Anderson Ibsen (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This paper aims analyze how educational activities involving literature in class, in a perspective of literacy, are able to develop critical and argumentative skills in the students, that is, can contribute to a reflective beings formation; beings with authorship evidences in their interlocutive activities and autonomy when in contact with language. Understanding that reflection activities on literary texts have the potential of forming active role readers in communicative relationship, we will base in Rildo Cosson's theory of literary literacy (2007), trying to understand how this process occurs among youngsters whose contact with literary works outside school is minimum or practically nonexistent, as well as understand how this cultural formation influences in the textual construction from the syntactic organization of the linguistic code.
Keywords: Literacy; Autonomy; Literature